Reduction of The Feeding Levels On Litopenaeus vannamei Nursery Under Bioflock Conditions - Sudaryono, Agung; Rostika, Rita (Indonesian Aquaculture Society (MAI), 2014)
The aim of this research was to evaluate whether the feeding levels in Litopenaeus vannamei nursery can be reduced without any adverse of the shrimp growth under bioflock conditions. There were 5 different reduced feeding levels as treatments in triplicates in this study ie. 10% reduction of the feeding level (A), 15% reduction of the feeding level (B), 20% reduction of the feeding level (C), 25% reduction of the feeding level (D), and no reduction of the feeding level (E; as control). Average daily gain (ADG) and water quality parameters were observed in the study. Results of the study showed that there were no significant differences (P>0.05) among all treatments with ranges of 0.11-0.19 g/day. It means that under bioflock conditions the feeding levels in the Litopenaeus vannamei nursery can be reduced up to 25% without any adverse in the growth performance.